Processioner i Nürnberg: De nationalsocialistiske rigspartidage under Det Tredje Rige, 1933-38 - Fiedler, Erik Sporon (Religionsvidenskabeligt tidsskrift, 2017)
The Nuremberg Party Rallies of the National Socialists are arguably the most important events on the special liturgical calendar of the Nazi-movement. A lot of the phenomena that make the Nazi movement a political religion are present at the rallies. The aim of this article is to give a thorough historical description of the events, especially the rallies that took place between 1933 and 1938, and to place them in a context where their significance to the study of religion becomes clear. The article begins with a brief discussion of the concept of political religion, and a historical account of the rallies is then given. Finally, the article considers the special relevance of the processions held during the rallies.